2001
DOI: 10.1093/emboj/20.20.5703
|View full text |Cite
|
Sign up to set email alerts
|

The nucleoporin Nup153 is required for nuclear pore basket formation, nuclear pore complex anchoring and import of a subset of nuclear proteins

Abstract: The nuclear pore complex (NPC) is a large proteinaceous structure through which bidirectional transport of macromolecules across the nuclear envelope (NE) takes place. Nup153 is a peripheral NPC component that has been implicated in protein and RNP transport and in the interaction of NPCs with the nuclear lamina. Here, Nup153 is localized by immunogold electron microscopy to a position on the nuclear ring of the NPC. Nuclear reconstitution is used to investigate the role of Nup153 in nucleo- cytoplasmic transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
191
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(215 citation statements)
references
References 68 publications
(140 reference statements)
24
191
0
Order By: Relevance
“…Indeed, previous work showed that depletion of NUP153 leads to import impairment of selective proteins. 16 Moreover, while we were conducting this study, Moudry et al 17 confirmed the mislocalization of 53BP1 in NUP153 depleted cells and showed the requirement of NUP153 for 53BP1 nuclear import.…”
Section: Resultssupporting
confidence: 61%
“…Indeed, previous work showed that depletion of NUP153 leads to import impairment of selective proteins. 16 Moreover, while we were conducting this study, Moudry et al 17 confirmed the mislocalization of 53BP1 in NUP153 depleted cells and showed the requirement of NUP153 for 53BP1 nuclear import.…”
Section: Resultssupporting
confidence: 61%
“…Membrane vesicles were bound to the chromatin surface, but they did not fuse to form a closed NE and no NPC assembly was detected either by immunofluorescence or electron microscopy. Of the nucleoporins thus far tested, depletion of only three have produced a similar defect in NE formation (Finlay et al, 1991;Powers et al, 1995;Grandi et al, 1997;Walther et al, 2001Walther et al, , 2002. Two nucleoporins are the integral pore membrane proteins NDC1 and POM121 Mansfeld et al, 2006) that reside, together with lamin B receptor, in a membrane vesicle population, which has a high avidity for the chromatin surface Ulbert et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Immuno-EM studies of the vertebrate Nup153 have clearly demonstrated a high degree of mobility and structural flexibility of its FG-repeat domain . Nup153 is a constituent of the nuclear basket of the NPC , where its N-terminal domain is anchored to the nuclear ring (Walther et al 2001;, while its central zincfinger domain resides at the distal ring . In contrast, the ∼700-residue long C-terminal domain of Nup153 harbors ∼40 FG-repeats and appears to be flexible within the NPC, as it can be detected at any place within the nuclear basket and may even reach through the central pore and appear at its cytoplasmic periphery .…”
Section: Nucleocytoplasmic Transport Across the Nuclear Pore Complex:mentioning
confidence: 99%